Rapid SERS detection of antimony using a superparamagnetic FA@MIL-101(Fe) composite substrate - Zhenli Sun; Jianghong Tang; Xunlong Ji; Jingjing Du (Environmental Chemistry and Ecotoxicology)
The pollution of antimony (Sb) and its accumulation as a persistent toxic substance (PTS) within environmental systems, leading to substantial hazards for ecosystems and public health. Therefore, developing rapid and sensitive methods for Sb detection is essential for mitigating its environmental impact. SERS presents a promising approach for detecting Sb, attributed to its high sensitivity and ability to capture distinct molecular fingerprints. However, traditional SERS substrates have struggled with effective detection because of weak interactions between Sb and traditional SERS substrate. To address this issue, a FA@MIL-101(Fe) composite combining Fe₃O₄’s magnetic properties and MIL-101(Fe)’s strong adsorption was synthesized, significantly enhancing Sb(III) detection. This substrate showed high sensitivity and selectivity, achieving a detection limit below 4 × 10−8 M, while effectively minimizing interference from other ions. Additionally, the substrate maintained long-term stability, consistently performing over 21 days. The FA@MIL-101(Fe) composite substrate offers a versatile and efficient platform for Sb(III) detection, providing broad potential for monitoring PTS in environmental applications.